The cerebral consequences of diabetes - Paula Jankowska; Krzysztof Jankowski; Ewa Rudnicka-Drożak; Grzegorz Mizerski (Kazimierz Wielki University, 2018)
Introduction The number of patients suffering from diabetes mellitus is growing globally. Diabetes is a disease requiring cooperation from the patient. Numerous cases of behavior not satisfying doctor are interpreted as lack of subordination and willingness to adapt to medical recommendations. Problems with adherence to treatment may be a result of decrease in cognitive functions, and associated cerebral diabetes complications as stroke, structural brain changes, depression and diabetic distress. Aim The purpose of this study is to present cerebral complications and their consequences depicted in professional literature. Results Diabetes has many severe cerebral complications. Patients may experience both ischaemic and haemorrhagic stroke and ensuing disability. Moreover, diabetes is described to be a serious factor contributing development of brain structural changes. There was decrease in of gray and white matter reported to be associated with decline in cognitive functions. Diabetes is also described as cause of depression and diabetic distress. These two affective problems are very serious reasons influencing everyday activity of patients. Glycaemic control in such individuals is significantly poorer than in people not suffering from these complications. Conclusions The cerebral complications of diabetes are frequent, especially in population of elderly people. They have substantial influence on cooperation with patient, treatment adherence and its outcomes. Every situation of doctor`s dissatisfaction with the results of diabetic education, compliance and self-care activities performed by the patient should lead to investigation if he have any diabetes cerebral complications.